2012
DOI: 10.4081/ejh.2012.23
|View full text |Cite
|
Sign up to set email alerts
|

An in situ hybridization study of the insulin-like growth factor system in developing condylar cartilage of the fetal mouse mandible

Abstract: The objective of this study was to investigate the involvement of the insulin-like growth factor (IGF) system in the developing mandibular condylar cartilage and temporomandibular joint (TMJ). Fetal mice at embryonic day (E) 13.0–18.5 were used for in situ hybridization studies using [35S]-labeled RNA probes for IGF-I, IGF-II, IGF-I receptor (-IR), and IGF binding proteins (-BPs). At E13.0, IGF-I and IGF-II mRNA were expressed in the mesenchyme around the mandibular bone, but IGF-IR mRNA was not expressed with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 34 publications
2
13
0
Order By: Relevance
“…While the underlying mechanisms responsible for this effect are currently unknown, previous studies suggest that the response of perichondrial cells to exogenous insulin and IGF-1 may be highly regulated. During development, perichondrial cells (compared to chondrocytes) express a higher proportion of IGF receptors (IGF-1R) [49], [50] and IGF binding proteins (IGFBP-4, IGFBP-5) [50]. The perichondrium also contains a population of chondrogenic progenitors (chondroblasts) [51], [52], which have been shown to differentiate into chondrocytes in response to exogenous IGF-1 [52].…”
Section: Discussionmentioning
confidence: 99%
“…While the underlying mechanisms responsible for this effect are currently unknown, previous studies suggest that the response of perichondrial cells to exogenous insulin and IGF-1 may be highly regulated. During development, perichondrial cells (compared to chondrocytes) express a higher proportion of IGF receptors (IGF-1R) [49], [50] and IGF binding proteins (IGFBP-4, IGFBP-5) [50]. The perichondrium also contains a population of chondrogenic progenitors (chondroblasts) [51], [52], which have been shown to differentiate into chondrocytes in response to exogenous IGF-1 [52].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have emphasised the role of TGF-β and insulin-like growth factor-I (IGF-I) as important mediators in promoting tissue repair through increased production of major articular cartilage matrix components. 27-30 However, the effect of TGF-β on matrix metabolism in chondrocytes is controversial. Conflicting reports have demonstrated that TGF-β leads to both increases 31,32 and decreases 33 in proteoglycan synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…7 Mandibular condylar cartilage differs somewhat from primary cartilage in, for example, its time of appearance, its cell alignment, the invasion pattern of capillaries, and the distribution of growth factors. 3,8,9 …”
Section: Introductionmentioning
confidence: 99%